The Compact with the Charter and Laws of the Colony of New Plymouth 115 (William Brigham ed., 1836) (changing Apr. 1 to Mar. 1) - (:unkn) unknown (My University, 1658)
Required that one quarter of each militia to be armed during Sunday church services. Each militia member required to have a firearm, sword, three charges of powder and bullets. Violators fined two shillies and six pence for each day's neglect.
Keywords: ARMED FORCES